THE ROLE OF CRITERION ASSESSMENT IN THE DEVELOPMENT OF EDUCATIONAL AND COGNITIVE ACTIVITY - Құрманова, Бақтыгүл; Оңғарбаева, Гүлмира; Балгазина, Бакитгуль (Pedagogy and Psychology, 2023)
The article is devoted to the problem of the development of educational and cognitive activity in the control and evaluation process in the modern field of education. Including the definition of the role of criteria-based assessment in the development of the educational and cognitive activity of the student. The purpose of this article is to reveal the essence of pedagogical and psychological educational and cognitive activity based on the theoretical positions and conclusions of scientists-teachers-psychologists. The analysis and conclusions made in the article can serve as an aid in the organization of educational and cognitive activity of the student in the process of implementing the criterion assessment. The authors used methods of analysis, synthesis, and comparison, and proved that criteria-based assessment plays an important role in the development of educational and cognitive abilities. The results obtained can help teachers of secondary and higher educational institutions and researchers with the theoretical aspect of the criteria-based assessment.